Le logement social aux Antilles (1946-1975) : une histoire post-coloniale des politiques publiques menées à la Guadeloupe et à la Martinique - Roméo Terral; Mario Selise (Caravelle)
In 1958, the cities of Pointe-à-Pitre (Guadeloupe) and Fort-de-France (Martinique) experienced a qualitative and quantitative housing crisis marked by the multiplication of spontaneous housing neighborhoods in the suburbs on the outskirts of the old colonial centers. To remedy this, real estate programs were carried out during the 1960s and 1970s. From these two examples, the aim is to determine what were the policies on social housing and habitat improvement in French West Indian cities.